Hubungan Romantis Serial Litte Mom dalam Perspektif Komunikasi Dakwah - Aulia Rini (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2022)
Romance Relationship Little Mom is one of the shows that raise dating values. This research aims to find out the value of Little Mom's romantic relationship from the perspective of Da'wah Communication. This research uses a qualitative approach with a discourse analysis approach—data collection using documentation and observation techniques. The results and conclusions of the study show that men and women who are not married together will lead interpersonal communication. If the effect produced from both is good, it will give birth to a sense of intimacy to encourage the creation of a romantic relationship. From the perspective of da'wah communication, the romantic relationship of unmarried couples is not recommended. This research can add to the scientific study of da'wah communication for researchers and academics in particular, as well as become an insight for the general public who are having an affair outside of marriage.